COVID-19’s Damages on International Stock Markets - Sylvia Susilo; Sukmawati Sukamulja (Universitas Hayam Wuruk Perbanas, 2022)
This research aims to analyze the effect of pandemic that hit the world: COVID-19 on return of the international stock market from March 11, 2020 until March 11, 2022. COVID-19 is measured by growth in cases and death. The novelty from this research is the use of 30 countries with the highest COVID-19’s cases. Methods of analysis used in this research are Error Correction Model (ECM) and Granger’s Causality Test using EViews 10. ECM’s result on X1 to Y show a significant effect on 22 countries in long-term and 22 countries in short-term. X2 and Y in ECM’s result show a significant effect on 23 countries in long-term and 26 countries in short-term. Two-way causality on X1 and Y occurred in 25 countries. Variables X2 and Y showed two-way causality on 28 countries. This research conducted to contribute for research and observation of the phenomenon that currently engulfing the world, COVID-19 pandemic.